Retrospective audit of patients referred for further treatment following Mohs surgery for non‐melanoma skin cancer. (18th January 2018) - Wee, Edmund; Goh, Michelle S; Estall, Vanessa; Tiong, Albert; Webb, Angela; Mitchell, Catherine; Murray, William; Tran, Phillip; McCormack, Christopher J; Henderson, Michael; Hiscutt, Emma L
Abstract: Background/Objectives: To describe the characteristics, subsequent management and outcomes of patients referred for further management following Mohs micrographic surgery (MMS) for basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Methods: Retrospective analysis of patients referred to a quaternary cancer centre from 2000 to 2015. Results: In total, 83 lesions in 82 patients were referred for further management; 52 (62%) were SCC and 80 (96%) were located in the head and neck. Reasons for referral included high‐risk disease for consideration for adjuvant radiotherapy (37/83, 45%), inadequate resection (28/83, 34%) or recurrence following previous MMS (15/83, 17%). Fewer than 40% of the 69 referrals received from MMS surgeons included photos or an operative report and diagram. There was discordance in pathology opinion in 11 (13%) of cases. Histopathology from MMS was reviewed in eight cases and there was discordance with the in‐hospital pathology opinion in six of these. In‐hospital re‐excision was performed in 19 cases and in five of these the pathology report on the paraffin‐sectioned re‐excised tissue was discordant with prior MMS assessment. Significantly, two cases were associated with a misinterpretation of lymphocytic infiltrate as residual disease in patients with chronic lymphocytic leukaemia (CLL). Conclusion: This study highlights some of the challenges and limitations of MMS. Early referral for multidisciplinary management is recommended when MMS resection margins are inadequate or uncertain, especially for high‐risk SCC. We recommend that referrals be accompanied by histological material, as well as a detailed report with operative photos and diagrams. CLL can pose an intraoperative diagnostic challenge. Discrepancies in the interpretation of MMS slides present an opportunity for improvement, and our findings support the role of ongoing quality assurance programs.